2014
DOI: 10.1371/journal.pone.0087143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of an Arterial-Spin-Labeling Product Sequence in Steno-Occlusive Disease of the Brain

Abstract: IntroductionIn brain perfusion imaging, arterial spin labeling (ASL) is a noninvasive alternative to dynamic susceptibility contrast-magnetic resonance imaging (DSC-MRI). For clinical imaging, only product sequences can be used. We therefore analyzed the performance of a product sequence (PICORE-PASL) included in an MRI software-package compared with DSC-MRI in patients with steno-occlusion of the MCA or ICA >70%.MethodsImages were acquired on a 3T MRI system and qualitatively analyzed by 3 raters. For a quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 38 publications
1
51
0
3
Order By: Relevance
“…ASL CBF imaging is obtained from the difference between the labeled and nonlabeled images and thus head motion (that cannot be canceled out) leads to artifact on ASL CBF image. In a recent study, Mutke et al found that the ASL images in 11 of 28 (39.3%) patients were uninterpretable due to head motion . Since commercial product ASL sequences (such as QUASAR‐PASL and FAIR‐PASL) are especially vulnerable to motion artifacts and only these commercial product ASL sequences can be used for clinical imaging, motion correction programs need to be made available in the clinical setting .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASL CBF imaging is obtained from the difference between the labeled and nonlabeled images and thus head motion (that cannot be canceled out) leads to artifact on ASL CBF image. In a recent study, Mutke et al found that the ASL images in 11 of 28 (39.3%) patients were uninterpretable due to head motion . Since commercial product ASL sequences (such as QUASAR‐PASL and FAIR‐PASL) are especially vulnerable to motion artifacts and only these commercial product ASL sequences can be used for clinical imaging, motion correction programs need to be made available in the clinical setting .…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between ASL and DSC measurements in cerebrovascular diseases has varied from modest to moderate‐or‐good . Siewert et al found agreement between the two imaging techniques in 17 of 21 (81%) patients with stroke, and that PASL could detect perfusion abnormalities in stroke similar to DSC MRI .…”
Section: Comparative Studies Between Asl and Pet/spect/dsc/dcementioning
confidence: 99%
“…This may be correct in patients with prolonged BAT and subsequent hypoperfusion but may be misleading in patients with prolonged BAT and normal perfusion which is often seen in chronic steno-occlusive disease. A recent study imaging at inflow times above 3000 ms showed that the perfusion values may in fact be normal in these areas and that only the BATs are prolonged, as evidenced by a high number of occurrences of the arterial transit delay artefact [17]. Thus, imaging at these long TIs might be necessary to avoid erroneous conclusions, which is especially important for a clinical use of ASL.…”
Section: Discussionmentioning
confidence: 99%
“…Raters were also asked to note the appearance of artifacts owing to increased ATTs, the "arterial transit delay artifact" (ATDA) in ASL-CBF maps. 24 Using the additional information provided by BAT maps, ATDAs were defined by the occurrence of dotted or serpiginous hyperintense areas in an area of low signal intensity in ASL-CBF with a corresponding increase of ASL-BAT in this area. 5,24 For calculation of sensitivity/specificity in the MCA territory, those cases were treated as hypoperfusion.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…24 Using the additional information provided by BAT maps, ATDAs were defined by the occurrence of dotted or serpiginous hyperintense areas in an area of low signal intensity in ASL-CBF with a corresponding increase of ASL-BAT in this area. 5,24 For calculation of sensitivity/specificity in the MCA territory, those cases were treated as hypoperfusion. Interrater agreement was assessed using Randolph's free-marginal multirater kappa (http://justusrandolph.net/kappa/).…”
Section: Qualitative Analysismentioning
confidence: 99%